KERAGAMAN PRANATA AGAMA DAN BUDAYA SERTA IMPLIKASINYA BAGI PENGUATAN KEGIATAN EKONOMI MASYARAKAT DESA - Rozuli, Ahmad Imron (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
The focus of this study was to map out how the dimensions of religious diversity in a rural area of environment has implications for community economic empowerment process. These dynamics is an interesting study, where the level of religious institutions as a symbol of a part in accelerating economic activity. The diversity of religious institutions, it becomes an attractive tourist icons that further increase the income of people in the village. The results of this study obtained data related to how the diverse aspects of religious institutions to support capacity for the process of strengthening community economic activities. Village Wonosari, Wonosari district, Malang regency is a tourist icon with the diversity of religious rituals such as Islam, Confucianism, as well as the ethnic diversity of Java, Madura and Tionghoa. Tourist icons is supported by the harmonization of diverse religious and social institutions that build a positive image in which the symbols of the religious activities are not separate, as well as limitless. This unique example, âmakam Kyai Zakaria/Eyang Jugoâ is an Islamic scholar but also the Confucian pilgrimage. This of course can not be separated from the stigma that continues to grow in some communities that ângalap berkahâ and Gunung Kawi as a place for